A Needs Analysis for English Speaking Syllabus Development - Dewi Yana (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2016)
This study aims at identifying the students’ needs in learning English speaking to promote speaking syllabus development. This research was a qualitative descriptive research. The subjects were 63 students of the first, third and fifth semester of English Education Study Program of Teacher Training and Education Faculty of Riau Kepulauan University. The data were collected using a questionnaire. The questioner is aimed at gathering information related to the target needs, and wants. The results found that the students target of studying English speaking are for their future profession and for their higher education. They want practicing the English speaking when they are studying, and they want enjoying a lot of speaking activities at the classroom together with their pair or group. They also want the speaking course exist as the English education study curriculum. The students assumed for the role of teacher as a facilitator and guide in the teaching learning activities. Keywords : needs analysis, speaking syllabus development